Changing ABRA protein peptide to fit into the HLA-DRbeta1*0301 molecule renders it protection-inducing (2004)
The Plasmodium falciparum acidic–basic repeat antigen represents a potential malarial vaccine candidate. One of this protein’s high activity binding peptides, named 2150 (161KMNMLKENVDYIQKNQNLFK180), is conserved, non-immunogenic, and non-protection-inducing. Analogue peptides whose critical binding residues (in bold) were replaced by amino-acids having similar mass but different charge were synthesized and tested to try to modify such immunological properties. These analogues’ HLA-DR?1* molecule binding ability were also studied in an attempt to explain their biological mechanisms and correlate binding capacity and immunological function with their three-dimensional structure determined by 1H NMR. A 310 distorted helical structure was identified in protective and immunogenic peptide 24922 whilst ?-helical structure was found for non-immunogenic, non-protective peptides having differences in ?-helical position. The changes performed on immunogenic, protection-inducing peptide 24922 allowed it to bind specifically to the HLA-DR?1*0301 molecule, suggesting that these changes may lead to better interaction with the MHC Class II-peptide-TCR complex rendering it immunogenic and protective, thus suggesting a new way of developing multi-component, sub-unit-based anti-malarial vaccines.